The Linking of User Experience, Application Quality, Customer Satisfaction, and Customer Loyalty on the Kopi Kenangan Application in Bandung City: A Conceptual Paper - Sheren Marselina; Arry Widodo; Nurafni Rubiyanti (International Publisher, 2026)
The acceleration of digital transformation in the food and beverage (F&B) industry after the COVID-19 pandemic has significantly shifted consumer behavior from offline transactions toward digital platform-based services. This condition encourages coffee retail companies to optimize mobile applications to improve customer engagement and retention. Kopi Kenangan, as one of Southeast Asia’s leading coffee-tech companies, faces challenges in maintaining customer loyalty amid intense competition in Bandung’s digital coffee market. This study aimed to develop a conceptual framework explaining the relationship between User Experience (UX), Application Quality, Customer Satisfaction, and Customer Loyalty within the Kopi Kenangan application ecosystem. This study employed a conceptual paper approach using a Systematic Literature Review (SLR) by synthesizing more than 30 peer-reviewed academic articles published between 2020 and 2025. The findings indicate that User Experience and Application Quality positively influence Customer Satisfaction, which subsequently strengthens Customer Loyalty. Furthermore, Customer Satisfaction was identified as a dominant mediating variable in the relationship between digital interaction quality and loyalty. This study formulated seven conceptual propositions that can be empirically tested in future research using SEM-PLS approaches. The study also provides theoretical and practical implications for improving digital customer retention strategies in the app-based coffee retail industry.